THE EFFECT OF LEVEL OF WORKING PARTICIPATION (TPAK) AND LEVEL OF OPEN (TPT) UNEMPLOYMENT ON ECONOMIC GROWTH IN ACEH 2007-2015 - Nadia Ulfa; Hijri Juliansyah (Journal of Malikussaleh Public Economics, 2018)
This study aims to determine how much influence the Labor Force Participation Rate (TPAK) and the Open Unemployment Rate (TPT) have on Economic Growth in Aceh. This study uses secondary data obtained directly from relevant agencies from 2007-2015. The analytical method used in this study is a quantitative method using multiple linear regression models with the help of EViews version 9 and has passed the testing of classical assumptions. The results showed that the variable Labor Force Participation Level (X1) and Open Unemployment Rate (X2) had a significant and positive effect on economic growth in Aceh.